Perfil metagenómico en muestras de tracto intestinal de paloma domestica Columba livia (2022)
The domestic pigeon Columba livia is a synanthropic specie that inhabits and nests in highland interiors, coastal cliffs and in urban environments, and well-known host harboring several zoonotic pathogens. In Colombia, reports missed the presence of zoonotic pathogens in pigeons, limiting planning when controlling their spread. In this study, the bacterial microbiota of the intestinal tract was identified in 3 pigeons from a market place from Bogota through phenotypic and metagenomic studies. Results analyzed possible public health implications regarding the identified bacterial species.